Users’ perception towards energy efficient buildings / Nadzirah Zainordin, Siti Marina Abdullah and Zarita Ahmad @ Baharum - Abdullah, Siti Marina; Ahmad @ Baharum, Zarita (Faculty of Architecture, Planning and Surveying, 2012)
A well-designed energy efficient building maintains the best environment for human habitation while minimising the cost of energy.